1999
DOI: 10.1523/jneurosci.19-02-00783.1999
|View full text |Cite
|
Sign up to set email alerts
|

Lhx9: A Novel LIM-Homeodomain Gene Expressed in the Developing Forebrain

Abstract: A novel LIM-homeodomain gene, Lhx9, was isolated by degenerate RT-PCR followed by mouse embryonic library screening. Lhx9 cDNA encodes a protein that is most closely related to Drosophila apterous and rodent Lhx2 proteins. The Lhx9 spatiotemporal pattern of expression during embryogenesis was similar but distinct from Lhx2. Highest expression levels were found in the diencephalon, telencephalic vesicles, and dorsal mesencephalon. Domains of expression respected the proposed neuromeric boundaries (). Lhx9 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
158
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(175 citation statements)
references
References 40 publications
(56 reference statements)
13
158
2
1
Order By: Relevance
“…Also ISH and TRAP may differ because of differences between transcription and translation, and occasionally ISH from the Allen Brain Atlas are simply inaccurate. For example, Lhx9 shows strong ubiquitous brain expression in the Allen Brain Atlas at most ages, in contrast to other reports (Bertuzzi et al 1999;Retaux et al 1999;Nakagawa and O'Leary 2001;Gray et al 2004). Nonetheless, even using only the 188 transcripts derived from our most number of transcripts to score, but of their scorable ISH patterns, they showed nearly the same pattern of enrichment as the TRAP data (57% with scores of 1-3).…”
Section: Comparison With Previous Studies and Validation Of Microarracontrasting
confidence: 94%
“…Also ISH and TRAP may differ because of differences between transcription and translation, and occasionally ISH from the Allen Brain Atlas are simply inaccurate. For example, Lhx9 shows strong ubiquitous brain expression in the Allen Brain Atlas at most ages, in contrast to other reports (Bertuzzi et al 1999;Retaux et al 1999;Nakagawa and O'Leary 2001;Gray et al 2004). Nonetheless, even using only the 188 transcripts derived from our most number of transcripts to score, but of their scorable ISH patterns, they showed nearly the same pattern of enrichment as the TRAP data (57% with scores of 1-3).…”
Section: Comparison With Previous Studies and Validation Of Microarracontrasting
confidence: 94%
“…Of the set of 17 LIM genes comprising Lhx1-9, Lmx1a, 1b, Isl1, 2, and Lmo1-4, we focused on only those genes for which our preliminary studies or published reports from other groups showed expression in the dorsal telencephalon (Boehm et al, 1991;Foroni et al, 1992;Fujii et al, 1994;Porter et al, 1997;Sheng et al, 1997;Kenny et al, 1998;Bertuzzi et al, 1999;Retaux et al, 1999;Millonig et al, 2000). Lhx3,4,6,7,8,Lmx1b, and Isl1, 2 were excluded because previously reported expression patterns reveal their expression to be in only ventral but not dorsal telencephalon, or restricted to nontelencephalic CNS regions, in addition to non-CNS structures (Thor et al, 1991;Li et al, 1994;Tsuchida et al, 1994;Zhadanov et al, 1995;Yamashita et al, 1997;Chen et al, 1998;Grigoriou et al, 1998;Kitanaka et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…LOC400800 was not expressed at all, suggesting that this putative gene of unknown function (Ota et al, 2004) does not play a role in these tissues. Similarly, it is not surprising that LHX9, a transcription factor involved in nervous system and urogenital development (Bertuzzi et al, 1999;Retaux et al, 1999), is not found in breast tissue or cell lines (Figure 4a), nor is it unusual that PTPRC (CD45), a leukocyte marker (Trowbridge et al, 1991), is not expressed in breast cancer cell lines. The expression of PTPRC in retinoblastoma, HR (Figure 3b), and normal breast (Figure 4a) may be attributable to infiltration of immune cells into these tissues.…”
Section: Discussionmentioning
confidence: 98%